Inhibition of mild steel corrosion in HCl solution using amino acid L-tryptophan - Mobin, M; Parveen, Mosarrat; Khan, M Alam (Recent Research in Science and Technology, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The corrosion inhibition characteristics of nitrogen containing amino acid L-tryptophan on mild steel in 0.1 M HCl solution was studied by weight loss and potentiodynamic polarization measurements. L-tryptophan significantly reduces the corrosion rates of mild steel; the maximum inhibition efficiency being 83% at 50 oC in presence of inhibition concentration of 500 ppm. The adsorption of inhibitors on mild steel surface obeyed Langmuirâ€™s adsorption isotherm. The calculated thermodynamic parameters for adsorption reveal a strong interaction between the inhibitors and the mild steel surface. The results obtained by electrochemical studies are consistent with the results of the weight loss measurement. L-tryptophan acts more anodic than cathodic inhibitor.